Hubungan Pengetahuan Wanita Usia Subur (WUS) tentang Pemeriksaan Pranikah dengan Sikap WUS dalam Pemeriksaan Pranikah di Tanjung Pinang Tahun 2014 - Fidyah Aminin; Fitri Mariyani; Tiyara Safitri (STIKes Patria Husada Blitar, 2015)
Based on Indonesian Demographic and Health Survey in 2008, there were 80,000 newborns died. One possible cause was infection. Infections acquired from placenta transplant from mother to fetus can cause congenital abnormalities such as TORCH infections. This can be prevented by doing premarital examination. This study investigated the relationship between childbearing women’s knowledge about premarital examination and attitude in premarital examination in Tanjungpinang in 2014. This was an analytic study with a cross-sectional research design. Location was selected in Tanjungpinang on June 12 to June 23, 2014. The sampling was done by purposive sampling technique. The sample was 47 people. Instrument used was a questionnaire and data collection was done by filling the questionnaire. The obtained data was analyzed with chi-square test. The results showed that, of the 47 respondents, 87.2% had high knowledge with 68.1% having a positive attitude while 12.8% had low knowledge with 31.9% having a negative attitude. The results of the chi-square statistical test obtained a pvalue of 0.009 (p <0.05), then H0 was rejected, meaning that there was a correlation between childbearing women’s knowledge about premarital examination and attitude in premarital examination in Tanjungpinang in 2014. It was suggested that the childbearing women expected to undergo premarital examination before marriage. It was recommended to the Health Clinic Laboratory to improve the premarital screening program with promotional efforts.